Exploring the utility of the Prescribing Safety Assessment in pharmacy education in England: experiences of pre‐registration trainees and undergraduate (MPharm) pharmacy students. (8th August 2018) - Hardisty, Jessica; Davison, Kathryn; Statham, Louise; Fleming, Gail; Bollington, Lynne; Maxwell, Simon
Abstract: Objectives: (i) To provide a preliminary indication of the performance of pharmacy undergraduate students and pre‐registration pharmacy trainees in the Prescribing Safety Assessment (PSA). (ii) To determine the feasibility of administering and delivering the PSA in schools of pharmacy. (iii) To examine the potential relevance of the PSA and associated training materials to pharmacy education. (iv) To assess the attitudes of the cohort towards the PSA and their readiness to prescribe. Methods: Four schools of pharmacy in England recruited final year undergraduate pharmacy students and pre‐registration pharmacy trainees undertaking training with both hospital and community pharmacy employers in their locality to undertake the PSA. Performance data and feedback from candidates were obtained. Key findings: Pre‐registration pharmacy trainees in community ( n = 27) and hospital ( n = 209) settings mean average scores were 86.3% and 85.3%, respectively. There was a significant performance differential between undergraduate pharmacy students ( n = 397) and those in pre‐registration training, with the mean average score for undergraduate students being 73.0% ( t test P < 0.05). Candidates felt their current course did prepare them for the PSA, some highlighted that additional curriculum content would be needed should this become a compulsory high‐stakes assessment for pharmacy trainees. The majority of candidates felt that this assessment was useful and applicable to their training. Conclusions: The PSA process and associated learning tools could be introduced to pre‐registration pharmacy education to support trainees in their development towards future prescribing roles.